Antibiotics - Yes or No? - Mosier, J.E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
From January, 1976, to January, 1977, I served as chairman of a subcommittee of the National Advisory Food &Drug Consultants charged with examining several issues concerned with the "Use of Antibiotics in Animal Feeds". It was through the activities of this subcommittee that I have had the opportunity to review papers and to hear presentations and discussions by many knowledgeable people concerning such use. Most of you are fully cognizant that the use of antibiotics in animal feeds originated from the observations of Jukes and Stokstad in 1949. Subtherapeutic levels are used for increasing weight gain, improving feed efficiency, and preventing or controlling animal disease. In 1973 in the United States, 20.8 million pounds of antibiotics were produced--12.6 million destined for medicinal use and 8.2 million pounds for nonmedical use, primarily in animal feeds.
Bright Future? is known as Swine Day, 1977
Keywords: Swine; Antibiotics; Subtherapeutic